2019
DOI: 10.4103/ijo.ijo_1852_18
|View full text |Cite
|
Sign up to set email alerts
|

Challenges during femtosecond laser assisted cataract surgery with posterior chamber phakic intraocular lens

Abstract: Femtosecond laser-assisted cataract surgery was performed in a patient with high myopia, who had undergone posterior chamber phakic intraocular lens surgery (Implantable Collamer Lens, ICL). During docking the machine erroneously focused the laser on the anterior surface of ICL and laser for lens fragmentation was also defocused, which were correctly positioned before laser delivery. During laser application for capsulotomy, air bubbles were entrapped under the ICL prohibiting lens fragmentation. One must be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Femtosecond laser-assisted cataract surgery (FLACS) combined with ICL extraction has been shown to be a feasible method for patients developing cataracts after the ICL implantation [180][181][182][183]. We can also proceed for ICL explanation with cataract surgery and IOL insertion of the affected eye [184].…”
Section: Cataractmentioning
confidence: 99%
“…Femtosecond laser-assisted cataract surgery (FLACS) combined with ICL extraction has been shown to be a feasible method for patients developing cataracts after the ICL implantation [180][181][182][183]. We can also proceed for ICL explanation with cataract surgery and IOL insertion of the affected eye [184].…”
Section: Cataractmentioning
confidence: 99%
“…It has been reported that incomplete nuclear fragmentation can be more common when performing FLACS in the presence of anterior or posterior chamber PIOLs [8,9]. Incomplete nuclear fragmentation has been attributed to bubble accumulation beneath the PIOL which can also be responsible for incomplete capsulotomy [9]. Other reported challenges are related to the docking procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have described the successful use of FLACS in a case with posterior chamber pIOL in situ. [3] They manually adjusted the laser treatment zone to avoid laser delivery to the implantable collamer lens (ICL) and observed accumulation of cavitation bubbles beneath the ICL hampering successful nuclear fragmentation.…”
mentioning
confidence: 99%
“…It is essential to manually adjust the treatment zone, and various modifications in laser parameters have been suggested for optimal results including increasing the depth and vertical spot spacing of capsulotomy as well as increasing the safety zones of anterior and posterior lens capsules during nuclear fragmentation. [345]…”
mentioning
confidence: 99%
See 1 more Smart Citation